The impact of magnesium–aluminum-layered double hydroxide-based polyvinyl alcohol coated on magnetite on the preparation of core-shell nanoparticles as a drug delivery agent - Ebadi, Mona; Buskaran, Kalaivani; Saifullah, Bullo; Fakurazi, Sharida; Hussein, Mohd Zobir (MDPI, 2019)
One of the current developments in drug research is the controlled release formulation of drugs, which can be released in a controlled manner at a specific target in the body. Due to the diverse physical and chemical properties of various drugs, a smart drug delivery system is highly sought after. The present study aimed to develop a novel drug delivery system using magnetite nanoparticles as the core and coated with polyvinyl alcohol (PVA), a drug 5-fluorouracil (5FU) and Mg–Al-layered double hydroxide (MLDH) for the formation of FPVA-FU-MLDH nanoparticles. The existence of the coated nanoparticles was supported by various physico-chemical analyses. In addition, the drug content, kinetics, and mechanism of drug release also were studied. 5-fluorouracil (5FU) was found to be released in a controlled manner from the nanoparticles at pH = 4.8 (representing the cancerous cellular environment) and pH = 7.4 (representing the blood environment), governed by pseudo-second-order kinetics. The cytotoxicity study revealed that the anticancer delivery system of FPVA-FU-MLDH nanoparticles showed much better anticancer activity than the free drug, 5FU, against liver cancer and HepG2 cells, and at the same time, it was found to be less toxic to the normal fibroblast 3T3 cells.